Shear strength and deformation characteristics of geosynthetic soil bags stacked horizontal and inclined. Issue 2 (1st April 2008) - Matsushima, K.; Tatsuoka, F.; Mohri, Y.; Aqil, U.
Abstract : The strength of stacked soil bags is very low when sheared laterally, compared with the strength when compressed vertically. To substantially increase the stability of soil structures composed of stacked soil bags, this paper proposes inclined stacking of soil bags so that the compressive stress on the bag-to-bag interface increases. A series of lateral shear loading tests were performed on a pile of three full-scale soil bags stacked horizontally ( δ = 0°) as well as inclined ( δ = 18°) at different vertical confining pressures (30 kPa, 150 kPa and 300 kPa). Two types of backfill material were used: a poorly graded fine sand and a well-graded sandy gravel. The shear strength of the soil bags was considerably larger when stacked inclined than when stacked horizontally. With soil bags of sandy gravel, whether stacked horizontally or inclined, failure was dominantly always by slippage along the bag-to-bag interface. With soil bags of Toyoura sand, when stacked inclined at high confining pressure, failure was induced by shear failure in the backfill. It is shown that the method of inclined stacking method at a suitable angle is simple and cost-effective. It is also important to compact soil bags in advance, and to use well-graded coarse backfill to increase the interface friction angle, the strength of the backfill and the confining pressure in the backfill. The strength of stacked soil bags is very low when sheared laterally, compared with the strength when compressed vertically. To substantially increase the stability of soil structures composed of stacked soil bags, this paper proposes inclined stacking of soil bags so that the compressive stress on the bag-to-bag interface increases. A series of lateral shear loading tests were performed on a pile of three full-scale soil bags stacked horizontally ( δ = 0°) as well as inclined ( δ = 18°) at different vertical confining pressures (30 kPa, 150 kPa and 300 kPa). Two types of backfill material were used: a poorly graded fine sand and a well-graded sandy gravel. The shear strength of the soil bags was considerably larger when stacked inclined than when stacked horizontally. With soil bags of sandy gravel, whether stacked horizontally or inclined, failure was dominantly always by slippage along the bag-to-bag interface. With soil bags of Toyoura sand, when stacked inclined at high confining pressure, failure was induced by shear failure in the backfill. It is shown that the method of inclined stacking method at a suitable angle is simple and cost-effective. It is also important to compact soil bags in advance, and to use well-graded coarse backfill to increase the interface friction angle, the strength of the backfill and the confining pressure in the backfill.